Estimation of Composition for Depropanizer Column Using Neural Network - Noor Zulkifli, Nur Amalina (Universiti Teknologi PETRONAS, 2016)
Artificial Neural Network provides better predictions for product quality in chemical process control. It is a systematic approach that will help to enhance the product quality by forecasting the top composition of propane for the depropanizer column. The technology of Neural Network also has the capability to analyse various complicated data in order to extract patterns and detect powerful trends for the system so that the generated model can be used to overcome any inappropriate issues related to end product properties. The objective of this study is to investigate and explore the use of neural network approach for the prediction of product quality.